2022
DOI: 10.3390/diagnostics12071730
|View full text |Cite
|
Sign up to set email alerts
|

Effective Prevention and Management Tools for Metabolic Syndrome Based on Digital Health-Based Lifestyle Interventions Using Healthcare Devices

Abstract: Digital health-based lifestyle interventions (e.g., mobile applications, short messaging service, wearable devices, social media, and interactive websites) are widely used to manage metabolic syndrome (MetS). This study aimed to confirm the utility of self-care for prevention or management of MetS. We recruited 106 participants with one or more MetS risk factors from December 2019 to September 2020. Participants were provided five healthcare devices and applications. Characteristics were compared at baseline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…33 The use of E-Health apps in most cases is voluntary, but persistence to goals can set the stage for long-term use, thereby promoting more favorable health outcomes. 34 The use of digital health-based lifestyle interventions may increase engagement and persistence in self-healthcare, 35 which is essential in the case of the syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…33 The use of E-Health apps in most cases is voluntary, but persistence to goals can set the stage for long-term use, thereby promoting more favorable health outcomes. 34 The use of digital health-based lifestyle interventions may increase engagement and persistence in self-healthcare, 35 which is essential in the case of the syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous pieces of evidence suggest that patients who were identified with MS tend to have a higher risk of developing depression and a lack of support for social activities that help them to implement self-management behaviors such as exercise and diet [ 45 , 46 ]. Simultaneously, poor diabetic self-management behaviors may lead to the development or worsening of MS [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was able to detect COVID-19 in the pre-symptomatic period as well as the symptomatic phase of the patients, with a precision score of 0.91 (CI: 0.854–0.967) [ 10 ]. Cho et al proposed a one-class SVM method that can detect COVID-19 23.5–40% earlier compared to the method of Mishra et al [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ,…”
Section: Wearables As Digital Diagnosticsmentioning
confidence: 99%
“…Hence, wearables provide a non-invasive, miniaturized, easy-to-operate, and novel method for glucometry, which could be used as an alternative to invasive tools in clinical settings [ 83 ]. In another study reported by Lee et al, smartwatch data along with other digital data were used to enable the better prevention of metabolic syndromes by the continuous detection of several health factors [ 41 ].…”
Section: Wearables As Digital Diagnosticsmentioning
confidence: 99%